Investigating the structural relationship of mass media on attitude, social influence, product safety and its impact on purchase behaviour of herbal product in Malaysia - Sarina, Ismail; Nur Aishah, Awi; Monizaihasra, Mohamed; Yusliza, Mohd Yusof; Jumadil Saputra, Aswin Ibrahim; Ramayah, Thurasamy (Growing Science., 2021)
Mass media is a crucial advertising platform and serves as an awareness platform for herbal product businesses. The rising popularity of herbal product consumption is due to the changing of lifestyle and health problems. With the increasing demand for herbal products globally, studies related to the herbal products purchase behaviour are considered very limited. Hence, the current study is written to investigate the structural relationship of mass media on attitude, social influence, product safety and its impact on purchase behaviour of Herbal products in Malaysia. By applying the AttitudeBehaviour Context Theory, this study used several variables, namely mass media toward attitude, social influence, and product safety and purchasing behaviour of herbal products. This study was designed using a quantitative approach through a survey questionnaire. A total of 467 respondents from seven states in Peninsular Malaysia have participated in this study and collected using the intercept survey. The data were analysed using structural equation modelling with a partial least square approach (SEM-PLS) and assisting SmartPLS 3.3.3. The results showed that mass media has a significant positive effect on attitude, social influence and product safety. Also, attitude, social influence and product safety have a significant positive impact on the purchase behaviour of herbal products. In conclusion, this study identified that mass media influence on attitudes is the strongest predictor, followed by the effects of the mass media on social influence. These findings indicated that the mass media play an essential role in influencing attitude, social influence, and product safety. Followed by attitude, social influence, and product safety that significantly impact the purchase behaviour of herbal products. The finding of this study provides insightful information to the entrepreneurs regarding consumers purchase behaviour.